Exciton Lasing in ZnO-ZnCr2O4 Nanowalls - Tejendra Dixit; Jitesh Agrawal; Miryala Muralidhar; Masato Murakami; Kolla Lakshmi Ganapathi; Vipul Singh; M. S. Ramachandra Rao (IEEE Photonics Journal, 2019)
We demonstrate low power continuous wave, red and NIR exciton lasing with FWHM of 1 nm, quality factor of 680 and threshold power of 100 μW in ZnO-ZnCr2O4 nanowalls. The NIR lasing was enabled by integrating ZnO with ZnCr2O4. Moreover, wavelength selective photoluminescence (tuning from UV to NIR) and enhanced two-photon emission were also observed in ZnO-ZnCr2O4 nanowalls. The exciton-exciton scattering can be attributed to the observation of exciton lasing at low temperature (<200 K). A plausible mechanism has been elucidated in order to explain the results. This work will open new opportunities in the advancement of oxide semiconductors based exciton lasers.